The relationship of nursing students' personality traits with their perceived stress in clinical environment - Seyed Kazem Mousavi; Mohsen Kamali (Kashan University of Medical Sciences, 2021)
Background: Clinical education is the most stressful part of education for nursing students. This study investigated the relationship of nursing students' personality traits with their perceived stress in clinical environment. Objectives: This study aimed at investigating the relationship of nursing students' personality traits with their perceived stress in clinical environment. Methods: This cross-sectional study was conducted in October 2020 on 215 nursing students. Participants were selected through stratified random sampling from Zanjan University of Medical Sciences, Zanjan, Iran. Data collection instruments were a demographic questionnaire, the NEO Personality Inventory short form, and the Perceived Stress Scale. Data analysis was done through the independent-samples t-test, Pearson's correlation analysis, and one-way analysis of variance. Results: The mean score of perceived stress was 43.74±10.25 out of 56, implying high level of stress. Neuroticism personality trait had significant positive correlation with perceived stress (P < 0.001), whereas extraversion and agreeableness personality traits had significant negative correlations with perceived stress (P < 0.05). Conclusion: Healthcare authorities need to employ strategies to identify nursing students who are at risk for stress and improve their psychological readiness for attending clinical environment.